2019
DOI: 10.1002/ejhf.1380
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates and outcome associated with changes in 6‐minute walking distance in patients with heart failure: findings from the BIOSTAT‐CHF study

Abstract: Background The 6‐minute walk test (6MWT) is a simple and inexpensive way of measuring exercise capacity in patients with heart failure (HF) that predicts morbidity and mortality. However, there are few reports from large multicentre cohorts assessing the predictive value of baseline and changing walk distance. Methods and results In BIOSTAT‐CHF, a 6MWT was performed at baseline (n = 1714) and 9 months (n = 1520). Cox proportional hazards models were used to assess the associations between 6MWT distance and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…However, performing CPET routinely is expensive and requires specialized and properly trained team. Considering larger studies that used different patterns of group division, worse prognosis was observed in patients who walked less than 360 meters, which makes the 6MWT an independent predictor of mortality in HF [5,11]. We emphasize that our results show convergence with other studies, despite differences regarding sample size and follow-up period.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, performing CPET routinely is expensive and requires specialized and properly trained team. Considering larger studies that used different patterns of group division, worse prognosis was observed in patients who walked less than 360 meters, which makes the 6MWT an independent predictor of mortality in HF [5,11]. We emphasize that our results show convergence with other studies, despite differences regarding sample size and follow-up period.…”
Section: Discussionsupporting
confidence: 70%
“…13 Nevertheless, its use can be useful in specialized services in clinical practice, as it is an objective and low-cost tool. (12,5) 6 (30,0) 0,09…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also a decrease in the 6MWT after 9 months was associated with a worse prognosis (adjusted HR for each 50 m decrease 1.09, 95% CI 1.06–1.12). The 6MWT distance was not changed by treatment up‐titration …”
Section: Exercise Capacitymentioning
confidence: 95%
“…The prognostic value of the 6‐minute walk test (6MWT) distance was analysed in the patients enrolled in the systems BIOlogy Study to TAilored Treatment in Chronic HF (BIOSTAT‐CHF) . Patients in the lowest and middle 6MWT tertile had poorer outcomes, compared to those in the highest tertile (>360 m) [adjusted hazard ratio (HR) 1.73, 95% confidence interval (CI) 1.38‐2.18].…”
Section: Exercise Capacitymentioning
confidence: 99%